Sistem Pendukung Keputusan Pemilihan Rumah Sakit Terbaik Di Kota Pematangsiantar Dengan Menggunakan Metode TOPSIS - Sanri Sunervia Yunika Damanik; S Saifullah; Riki Winanjaya (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
A hospital is a place where health services are provided by doctors, nurses and other health professionals. Health is the most important thing that every human wants to survive in doing all activities. The importance of this health encourages the government and the private sector to build quality hospitals so that people can access health needs. However, it is not only quality that is desired by the community, but satisfaction in providing fast services, supporting facilities and hygiene and safety are needed by the community so that the healing process feels happy and safe. To find out which hospital has the provision of health services desired by the community, a decision support system is needed. Decision support system is a system that can be used as a tool assist in the selection of hospitals that are in charge based on criteria desired by the community. The method used by researchers is the Topsis method. This method was chosen because it is able to select alternatives from several alternatives based on predetermined criteria. The results of this study are an average value of each alternative and criteria that will be ranked as the best hospital in Pematangsiantar. Based on the results of these tests can be a foundation that can help the community in choosing the provision of hospital services for the healing process.